HUBUNGAN DISFUNGSI EREKSI PADA PENDERITA DIABETES MELITUS TIPE 2 TERHADAP KUALITAS HIDUP DI POLIKLINIK PENYAKIT DALAM RSUP SANGLAH PROVINSI BALI - Muhammad Aris Sugiharso; Made Ratna Saraswati (Universitas Udayana, 2016)
Erectile dysfunction was one of the complication of diabetes mellitus that often ignored. Besides, erectile dysfunction could be a sign of uncontrolled blood glucose and microvascular complication. This condition coexist with strict management of therapy will cause the psychological distress to the patient and will affect his health-related quality of life. This study purposed to determine the prevalence of diabetic man with erectile dysfunction, quality of life and its relation with the quality of life. This study used the cross – sectional descriptive and analytic design that held on Outpatient Department of Diabetic Sanglah General Hospital Center Bali with 34 participants enrolled in this research. The International Index of Erectile Function (IIEF) 15 quissionaire given to assess the erectile dysfunction, Diabetic Distress Scale (DDS) to assess the psychological pressure and RAND Short Form (SF) 36 to assess the quality of life of patient. From this study found that the prevalence of erectile dysfunction is 61.8%. From Kruskal – Wallis test found that the decrease of quality of life, particularly in physical functioning, role limitations due to physical health, energy / fatigue, social functioning and general health domain, meanwhile with DDS questionnaire found the value of p>0.05 on all of the domain so that it concluded that there is no association between erectile dysfunction on diabetic patient with diabetic-related distress. From the Pearson correlation test found that the medium correlation (0.4 – 0.6) between erectile dysfunction on diabetic patient with physical functioning, emotional well-being and social functioning. Weak correlation (0.4) found on energy/fatigue and general health domain. The correlation was negative, which mean that higher the score of dysfunction on the patient will give the lower quality of life. It can be concluded that from this study found that there is a association between erectile dysfunction on diabetic patient and their quality of life. Meanwhile, there is no association between erectile dysfunction with the diabetic-related stress.